Pengaruh Live Streaming Selling dan Discount Pada Tiktok Shop - Rolando, Benediktus; Angelica, Natasya (ARBITRASE: Journal of Economics and Accounting, 2024)
This study examines the influence of Live Streaming Selling and discounts on Impulse Buying  behavior among Gen Z on the TikTok Shop platform. The objective of this research is to understand how these two factors can trigger impulsive purchasing decisions among young users. The type of research conducted is quantitative, with a sample of 99 respondents who are students aged 17-27 years actively using TikTok. Data collection was carried out through the distribution of questionnaires containing a Likert scale to measure respondents' perceptions. Data analysis was performed using quantitative descriptive and correlational methods to determine the relationship between the variables. The results indicate that Live Streaming Selling has a significant influence (t=2.242, p=0.027) and discounts also have a significant effect (t=2.018, p=0.046) on Gen Z's Impulse Buying  behavior. Simultaneously, both variables demonstrate a strong influence (F=29.707, p<0.05) with a determination coefficient (R²) of 0.382, indicating that 38.2% of the variation in Impulse Buying  behavior can be explained by these two factors. The implications of this research suggest that marketers need to integrate live streaming strategies with attractive discount offerings, enhance interactivity during live streaming sessions, and design discount programs tailored to Gen Z preferences. These findings also suggest the importance of maintaining live streaming content quality and timing discount offers to optimize their impact on impulse purchasing decisions.